KAJIAN USAHA PEMBESARAN IKAN DALAM KERAMBA JARING TANCAP (KJT) DI KELURAHAN SEDANAU KECAMATAN BUNGURAN BARAT KABUPATEN NATUNA PROVINSI KEPULAUAN RIAU - Hendrik, Hendrik (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
A study on fish enlargement in the static floating cage system aquaculture(FCSA) has been conducted in November 2014 in the Sedanau Village, BunguranBarat Sub-District, Natuna. This research aims to understand the prospect the businessbased on various investation criteria. The type of fish cultured were tiger grouper,grouper, humpback grouper and napoleon wrasse. Results shown that the amount ofinvestment for nine bags was Rp 204.55 million, seven bags was Rp 175.55 millionand 5 bags was Rp 141.2 million. The allocation fixed capital was 60% for boatpurchasingh, 25% for nets and 10% for other needs. The working capital was allocatedfor seed (45%) and feed (43%). Results of the investment analysis criteria such asRCR, FRR and PPC shown that the FCSA business with 5 bags per unit is better thanthe 7 and 9 bags per unit. The prospect of FCSA business is very good in terms ofmarketing and availability of food, but in the future, it may be difficulies in obtainingthe natural fish seed.